Treatment of Germ Cell Testicular Cancer - Ana Koši Kunac; Milena Gnjidić; Zrna Antunac Golubić; Marija Gamulin (Acta Clinica Croatica, 2020)
Germ-cell testicular cancer (GCTC) is a malignant neoplasm derived from the primordial germ cell. Although it accounts for approximately 1% of all malignancies in men, it is the most common cancer of younger male population, with the highest incidence between ages 15 and 35. Testicular cancer incidence rate has risen globally over the past several decades, with the average increase in the incidence of testicular cancer in Croatia of 7% per annum from the year 1983 to 2007. Two main groups are seminomas and non-seminomas, each accounting for 50% of cases, and they differ in treatment modalities and response to therapy. Despite increase in the incidence rate, a promising circumstance is that GCTC has become a model of curable cancer. Because of advances in diagnostic procedures, sophisticated radiation techniques and especially the introduction of cisplatin based chemotherapy protocols together with advanced postchemotherapy surgical techniques, curability is expected in about 95% of all patients diagnosed with testicular cancer and over 70% of patients with advanced disease. In this review, we will focus on treatment strategies of primary GCTC.